Violencia de Genero y Publicidad: Representaciones Sociales en un Grupo Poblacional en Edades Entre 18 A 50 Años Perteneciente al Barrio Bosa el Recreo (2016)
This research seeks to describe the social representations of gender violence related in the print advertising of seven participants of the Bosa El Recreo district aged between 18 to 50 years, delving into a group of men and women belonging to this neighborhood. To achieve the objective was implemented the theory which refers to social representations, gender violence and advertising imagery.